The importance of teaching pronunciation to produce stressed syllables - Albini, Andressa Brawerman (BELT - Brazilian English Language Teaching Journal, 2010)
This paper emphasizes the importance of teaching and practicing pronunciation in the classroom. Usually forgotten by teachers and students, this is a very important aspect of English not only to avoid accented speech, but also to avoid misunderstandings. An experiment which investigated the stress pattern of suffixed words produced by advanced Brazilian students of English was conducted in order to check possible problems caused by the lack of adequate teaching and the influence of Portuguese (the native language). It was observed that words with a stress pattern which is not usually practiced provide a large number of mistakes, showing that constant incorrect input, little correction and insufficient practice during classes provide great difficulty to students.